Redefining Islamic Pedagogy: A Transformative Approach to 21st-Century Education in Indonesian Pesantren - Taufikin, Taufikin (Maharot : Journal of Islamic Education, 2025)
This study aims to explore the implementation of transformative pedagogy in the context of pesantren education in the digital era, focusing on Al Mawaddah Entrepreneurial Islamic Boarding School in Kudus, Central Java. Employing a qualitative approach with a case study design, data were collected through in-depth interviews to fourteen informans with Kiai, Uztaz and Senior santri, participatory observation, and documentation. The discoveries appear this pesantren has successfully integrated Islamic values, entrepreneurial skills, and digital technology into the curriculum and daily learning practices. Strategies such as practice-based learning, integration of social media for da'wah and business, and 21st-century adaptive curriculum strengthen the relevance of pesantren education in facing global challenges. Despite facing challenges such as limited infrastructure and cultural resistance, pesantren shows excellent potential in shaping a contextualized and progressive model of Islamic education.